Nonthermal plasma-assisted catalysis NH3 decomposition for COx-free H2 production : A review - Awad, Omar I.; Zhou, Bo; Kadirgama, Kumaran; Chen, Zhenbin; Mohammed, M. N. (Elsevier Ltd, 2024)
Hydrogen (H2) is recognized as a viable and environmentally friendly energy source, utilized across various domains, from large-scale chemical energy exports to small-scale power generation in remote areas. However, the storage and distribution costs of H2 present significant challenges. Ammonia (NH3) emerges as a carbon-free hydrogen carrier, backed by a robust international transport and storage infrastructure. On-site hydrogen production can be efficiently achieved through NH3 decomposition, predominantly via thermal catalysis. One innovative approach involves plasma technology, which utilizes NH3, alcohols, or hydrocarbons to produce pure hydrogen in plasma reactors. Nonthermal plasma (NTP) in particular, for NH3 decomposition and H2 production, has garnered considerable interest owing to its higher energy efficiency than thermal plasma systems. Furthermore, integrating NTP with catalysis, termed plasma-assisted catalysis, creates a synergistic effect, enhancing NH3 decomposition efficiency for H2 production through improved plasma-catalyst interactions. Consequently, NTP-catalysis holds the potential to revolutionize NH3 conversion and utilisation in the future. To date, there have been limited studies on NTP-assisted catalytic NH3 decomposition. This review article compiles the latest NTP-assisted catalytic NH3 decomposition methodologies for H2 production. It delves into the basics of plasma-assisted NH3 decomposition, including adsorption, desorption, and the synergistic processes during plasma catalysis. Additionally, it examines the impact of NTP on the chemical states and properties of various catalysts and provides a comprehensive analysis of the factors influencing NH3-plasma decomposition.